Harnessing Energy from the Sun : Empowering Rooftop Owners - International Finance Corporation (New Delhi, 2017)
This white paper aims to create awareness - among stakeholders including policy makers, utilities, and regulators of the opportunities and challenges of the rooftop solar market. It focuses on implementation options, including public-private partnerships, and discusses practical issues related to planning and implementing rooftop solar initiatives. It discusses policy and technical issues that can help stakeholders make informed decisions, especially in terms of meeting local objectives. It presents how to involve rooftop owners and the private sector in developing the rooftop solar market while drawing on current international rooftop solar experience through case studies and interviews. It offers an overview of the nascent market in India, and specifically the Gujarat rooftop solar program. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.